Inhibition of Aldose Reductase Attenuates Endotoxin Signals in Human Non-pigmented Ciliary Epithelial Cells - Yadav, Umesh C S (2010)
Chronic inflammatory diseases such as autoimmune and bacterial infections are associated with an elevated risk of ocular inflammation. Ciliary epithelial cells that play an important role in maintaining aqueous humor dynamics and homeostasis of anterior segment of eye are continuously exposed to inflammatory markers during infections and injury. Lipopolysachharide (LPS), a gram negative bacterial endotoxin, dysregulates aqueous humor (AqH) homeostasis by inducing inflammatory changes. We have investigated how inhibition of a polyol pathway enzyme, aldose reductase (AR), alters LPS-induced inflammatory changes in human non-pigmented ciliary epithelial cells (hNPECs). The stimulation of hNPECs with LPS (1 μg/ml) caused increased secretion of inflammatory markers such as PGE(2) and NO in the culture medium as well as increased expression of COX-2 and iNOS proteins in cell extracts. LPS also increased phosphorylation of MAPKs (ERK1/2) and SAPK/JNK and activation of redox-sensitive transcription factors NF-κB and AP-1 in hNPECs and inhibition of AR by zopolrestat and sorbinil ameliorated these changes. Further, LPS-induced decrease in the expression of Na/K-ATPase in hNPECs was restored by AR inhibitors. Similar results were observed in ciliary bodies of LPS-injected rats. Taken together, our results suggest that AR plays an important role in the LPS-induced inflammatory changes in hNPECs and that inhibition of AR could be a novel therapeutic approach for ocular inflammation.